Peningkatan Motivasi Belajar Peserta Didik Melalui Model Pembelajaran Problem Based Learning - Darni Darni (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The aim of this research is to increase learning motivation in Class III students of Dukuh 1 State Elementary School in learning Mathematics through the Problem Based Learning (PBL) model. This research is classroom action research with four stages of activities, namely; (1) planning, (2) implementation; (4) observation; and (4) reflection. The research was carried out at Dukuh 1 State Elementary School with a total of 14 students as subjects. Data collection techniques use documentation and observation techniques. Data analysis techniques using qualitative analysis include; data reduction, data presentation, and collection and quantitative analysis including; average value and prosentase. Based on the results of data analysis, it can be concluded that the Problem Based Learning (PBL) learning model can increase the learning motivation of class III students at Dukuh 1 State Elementary School in learning Mathematics.